2018
DOI: 10.1038/s41598-018-34846-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural connectivity and neuroticism in healthy adults

Abstract: Understanding the neural correlates of the neurotic brain is important because neuroticism is a risk factor for the development of psychopathology. We examined the correlation between brain structural networks and neuroticism based on NEO Five-Factor Inventory (NEO-FFI) scores. Fifty-one healthy participants (female, n = 18; male, n = 33; mean age, 38.5 ± 11.7 years) underwent the NEO-FFI test and magnetic resonance imaging (MRI), including diffusion tensor imaging and 3D T1WI. Using MRI data, for each partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
2
16
0
1
Order By: Relevance
“…Accordingly, future investigations may apply graph theory ( Kaiser, 2011 ; Korgaonkar et al. , 2014 ; Ueda et al. , 2018 ; Pang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, future investigations may apply graph theory ( Kaiser, 2011 ; Korgaonkar et al. , 2014 ; Ueda et al. , 2018 ; Pang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results are thus rarely consistent (see Dima, Friston, Stephan, & Frangou, 2015;Gentili et al, 2017;B. J. Li et al, 2018;Ueda et al, 2018).…”
Section: N/ne In a Predictive-processing Modelmentioning
confidence: 96%
“…Comparing the cumulative number of shortest paths going through each brain region during the transition from a resting state to cognitive task evaluation, they found the gradual transition from a sharp decrease of betweenness across the parietal and frontal lobes in the delta range to a pronounced increase in the gamma range [168]. By constructing whole-brain inter-regional interactions for each participant, Ueda et al [169] found that the correlation between neuroticism and betweenness are very different for various brain regions, implying that the neuroticism trait is likely formed as a result of interactions among the brain regions related to neuroticism.…”
Section: Betweenness and Bottlenecksmentioning
confidence: 99%